The Influence of ChatGPT on Students' Information Literacy at SMA Negeri 1 Sungayang, Tanah Datar Regency, West Sumatra - Leffiatul Hanifa; Rini Asmara (Darul Yasin Al Sys, 2026)
The rapid advancement of artificial intelligence, particularly ChatGPT, has transformed how students access, evaluate, and manage information during learning. Although ChatGPT enables efficient information retrieval, its effective use requires adequate information literacy to critically assess and appropriately apply AI-generated content. This study aims to examine the influence of ChatGPT use on the information literacy of eleventh-grade students at SMA Negeri 1 Sungayang. A quantitative approach with a descriptive-explanatory design was employed, involving 69 students selected through simple random sampling. Data were collected using questionnaires developed based on the Technology Acceptance Model and the Big6 Information Literacy Model and analyzed using descriptive statistics, classical assumption tests, simple linear regression, a t-test, and the coefficient of determination. The findings demonstrate that ChatGPT use has a positive and significant effect on students’ information literacy (t = 10.814, p < .001), accounting for 63.6% of the variance in information literacy. The study concludes that appropriate ChatGPT use can support the development of students’ information literacy. These findings contribute to research on artificial intelligence-assisted learning by demonstrating the relationship between ChatGPT use and information literacy and imply that educational institutions should integrate AI tools with instructional practices that strengthen critical evaluation, responsible information use, and the application of AI-generated content.